Analysis of 5G Network Quality of Service on VoIP Application - Yuliani Putri, R.A Rizka Qori; Anhar, Anhar; Saputra, Anggi; Caniago, Rama Putra; Harianja, Rosarindo (International Journal of Electrical, Energy and Power System Engineering, 2024)
Based on the results of the research conducted, it can be concluded that the 5G network at Airport shows excellent performance in supporting the use of VoIP applications such as Instagram, WhatsApp, and Zoom. This is indicated by a consistent category 4 index on all measured parameters, namely throughput, packet loss, delay, and jitter. In terms of throughput, although there are variations between the three apps, all values are still sufficient to support voice and video calls with good quality. In fact, the lower throughput value on the Zoom app does not mean that the video call quality is poor, especially for one-on-one calls or with few participants. Furthermore, the absence of packet loss in all three applications indicates excellent connection stability. This is an important indicator showing that all the data sent and received by the apps made it to their destination without being lost midway, which is essential for ensuring clear voice and video quality. Meanwhile, very low delay and jitter indicate that data transmission is fast and consistent. This is especially important for real-time communications such as video calls, where delays or variations in the arrival time of data packets can disrupt call quality. Overall, the results of this study show that the 5G network at Airport is capable of supporting the use of VoIP applications with good quality. This is an important finding, given the importance of VoIP in everyday life, both for personal and professional communication. Therefore, this research hopes to make an important contribution in understanding and maximizing the potential of 5G network in supporting VoIP communication at Airport.